“Impeachment” ou “golpe”? uma análise dialógica do discurso sobre a crise política brasileira - Ferraz, Rodrigo Alan Feltrin (2019)
In this study, we seek to propose a dialogical analysis of the discourses that support the antinomic terms "impeachment" and "coup" as predicates for the Brazilian political crisis that occurred in 2016. Having found that two antagonistic terms have had social validation to qualify the same phenomenon, through discursive analysis, we seek to clarify relevant aspects of social relations at a given historical juncture. Our hypothesis is based on Valentin Volóchinov's (1895-1936) proposal that the ideologies that circulate socially materialized in the form of discourses are representations of the clashes of antagonistic social forces operating under the same set of signs. Accordingly, our general objective in this paper is to examine impeachment discourse and coup discourse based on the theoretical framework present in the works of the Bakhtin Circle, and our specific objective is to analyze, supported by the categories of enunciation as seen in the works of Volóchinov and his colleagues from the Circle, texts of official dissemination of political parties, which have the quality to serve as a display of each of these speeches. Our results indicate that, in their characterization of the political crisis of 2016, the opposition that the two terms represent in the ideological dispute of society has a verifiable basis in the materiality of its enunciations and reflects different social interests in dispute